Penampilan Produksi Domba Lokal di Desa Gucialit, Kabupaten Lumajang Berdasarkan Umur dan Jenis Kelamin - Achmad Iklilul L.L. As’ad; Meyya L. Zain; Gatot Ciptadi; Mudawamah; Khonita R. Diani (Jurnal Peternakan Nusantara, 2025)
This study was motivated by the importance of understanding the production performance of local sheep in Indonesia, particularly in Gucialit Village, Lumajang Regency, considering its significant role in meat production. This study aimed to examine the effect of age and sex on the production performance of local sheep, which includes body weight, chest girth, body length, and shoulder height. An observational method with a quantitative approach was employed. Local sheep were grouped based on sex (male and female) and age (<1 year, 1-1.5 years, and 1.5-2 years), followed by measurements of the aforementioned variables. Data were analyzed descriptively and statistically using a Completely Randomized Design (CRD). The results showed that age had a very significant effect (P<0.01) on all sheep production performance variables. As the age of the sheep increased, body weight, chest girth, body length, and shoulder height increased significantly. Sex differences also showed a significant effect on production performance. Male sheep had greater body weight, chest girth, body length, and shoulder height compared to female sheep within the same age group